Semi-automatic system to detect and evaluate multiple sclerosis lesions using magnetic resonance imaging. - Takahashi Ortiz, Jorge (Revista Mexicana de Ingenieria Biomedica, 2018)
A nuclear magnetic resonance imaging (NMR) image processing system is presented, applied to the quantitative study of the evolution of patients suffering from multiple sclerosis. The characteristics of the material used are described, as well as the programming developed.